SRIWEDARI MENJADI DESA INKLUSI BAGI PENYANDANG DISABILITAS MELALUI USAHA PENANAMAN POHON, KONSERVASI PENGUATAN TEBING DAN PENGHIJAUAN DALAM PENINGKATAN PRODUKTIVITAS - Dynaindar, Intan Jaya; Priyono, Nuwun (Transpublika Publisher, 2022)
Writing this article aims to provide an overview of the business form of Sriwedari Village to become a village that can develop a discourse on inclusive villages, develop disability-friendly services and increase the adaptive capacity of the community to climate change. In addition, it is also expected to increase the productivity of persons with disabilities in the village. This research uses descriptive research and a qualitative approach. Data collection techniques were obtained through literature study, interviews, observations, and documentation which were carried out directly in Sriwedari Village, Salaman District, Magelang Regency. The results of this study indicate that village initiatives are driven by awareness to increase productivity and fulfill the rights of persons with disabilities by involving them in tree planting efforts and also providing training to handle when a disaster strikes. The involvement of people with disabilities is expected so that people with disabilities have business skills in planting trees so that they can be independent entrepreneurs, know how to handle disasters that will occur, and most importantly they do not feel isolated in the community because they feel they are given more attention.